Evaluation of host immune responses to Mycobacteriophage Fionnbharth by route of delivery - Thomas Smytheman; Tiffany Pecor; Dana E. Miller; Debora Ferede; Suhavi Kaur; Matthew H. Harband; Hazem F. M. Abdelaal; Carlos A. Guerrero-Bustamante; Krista G. Freeman; Whitney E. Harrington; Lisa M. Frenkel; Graham F. Hatfull; et al. (Virology Journal)
Abstract For much of the last decade, tuberculosis (TB) was the leading cause of mortality due to an infectious pathogen (Mycobacterium tuberculosis, M.tb). Approximately 1.3 million deaths in 2023 worldwide were attributed to TB disease. Focused intervention strategies to block transmission would significantly reduce the global health burden of TB. Mycobacteriophages (phages) are a sorely underutilized biologic therapy for the pathogen M.tb, and here we aimed to address outstanding questions about their utility for clinical applications. We aimed to determine the impact of repeated mucosal or intravenous (IV) delivery of representative anti-M.tb phage FionnbharthΔ45Δ47 (Fionnbharth) in a preclinical mouse model. In addition, we specifically sought to understand which route induced anti-phage antibodies, which may reduce the long-term impact of phage therapy. C57BL/6 mice were dosed weekly for 6 weeks by either route and serum and bronchoalveolar lavage fluid (BALf) were evaluated for anti-phage humoral responses by ELISA. We found that aerosol delivery disperses phage across all lung lobes where M.tb is also found after experimental infection by the same route. Repeated aerosol delivery was well tolerated and did not induce robust neutralizing humoral immunity. In contrast, Mice receiving IV phage developed increasing magnitude and neutralizing total IgG and IgA responses over time. To determine whether pre-treatment environmental exposure to Fionnbharth-like phages could induce antibody responses that are potentially neutralizing, ~ 500 human plasma samples from normal donors were evaluated by ELISA. We observed that 5% of samples had antibodies to Fionnbharth (with end point titers > 10− 3 dilution), although none were neutralizing. Furthermore, we found that highly-purified phage preparations did not activate mouse or human derived toll like receptor (TLR) 4 or TLR9 in HEKblue reporter assays. These data together support using Fionnbharth in anti-M.tb therapy phage cocktail strategies and that aerosol delivery should be prioritized for further efficacy testing.